Flexible artificial synesthesia electronics with sound-synchronized electroluminescence. (May 2019) - Kim, Jong Sung; Cho, Sung Hwan; Kim, Kang Lib; Kim, Gwangmook; Lee, Seung Won; Kim, Eui Hyuk; Jeong, Beomjin; Hwang, Ihn; Han, Hyowon; Shim, Wooyoung; Lee, Tae-Woo; Park, Cheolmin
Abstract: Visualization of human senses has been of great interest for developing an emerging interactive display that can artificially stimulate synesthesia with numerous unprecedented applications. Especially, visualization of various daily sound and music, which are much more complicated than human touch, in a form of flexible thin film devices can be a great challenge. We present flexible artificial synesthesia electronics that visualize continuous and complicated sounds. The electronic device is made of a thin composite film of a piezoelectric polymer for sound generation and inorganic electroluminescence (EL) microparticles for direct visualization of input sound signals. Field-induced EL of the microparticles in the device depends upon the source sound wave, making their EL synchronized with sound arising from the piezoelectric actuation. The flexible artificial synesthesia devices with sound-synchronized EL (FASSEL) showed extreme mechanical tolerance that can be repeatedly folded and crumpled with visible sound, allowing a variety of unexplored applications including synchronous sound-lightings and wearable, on-body sound-vision systems to facilitate emotional interaction of human being with sound in a human-friendly form. Graphical abstract: Image 1 Highlights: Ultra-flexible piezoelectric loudspeakers were developed with sound synchronized EL. Piezoelectric polymer composite with EL particles for direct visualization of sound. Artificial synesthesia of sound and vision via a single capacitive device platform. Silica-encapsulated-ZnS particle was employed for high EL with low leakage current. Extreme mechanical tolerance that can be repeatedly folded and crumpled.